2013
DOI: 10.1007/s11552-013-9528-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy and Confidence in Distal Radius Volar Plate Screw Placement through Supplemental Radiography: Examining Specialty, Education, and Experience Levels

Abstract: A supplemental view of the distal radius combined with AP and lateral views significantly improves the ability of all evaluators, regardless of specialty or training level, to correctly assess placement of fixation screws. The greatest improvements are seen for resident trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Patel et al performed a survey of conventional and tilt views of 34 patients among 65 physicians. 41 They found that adding a 30-degree tilt lateral view to lateral and AP views increases the accuracy by 19%. 41 Sensitivity, specificity, and/or accuracy per imaging modality can be found in ►Table 5.…”
Section: Accuracymentioning
confidence: 99%
See 4 more Smart Citations
“…Patel et al performed a survey of conventional and tilt views of 34 patients among 65 physicians. 41 They found that adding a 30-degree tilt lateral view to lateral and AP views increases the accuracy by 19%. 41 Sensitivity, specificity, and/or accuracy per imaging modality can be found in ►Table 5.…”
Section: Accuracymentioning
confidence: 99%
“…41 They found that adding a 30-degree tilt lateral view to lateral and AP views increases the accuracy by 19%. 41 Sensitivity, specificity, and/or accuracy per imaging modality can be found in ►Table 5.…”
Section: Accuracymentioning
confidence: 99%
See 3 more Smart Citations